COMMUNITY PARTICIPATION IN SUPERVISION OF THE VILLAGE BUDGET IN BINUANG VILLAGE, BALUSU DISTRICT, BARRU DISTRICT - Aidah; Musdalifa; Asikin, Adrian (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal